2001
DOI: 10.1046/j.1445-6664.2001.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards an integrative biology research: a case study on adaptive and evolutionary trends of Miscanthus populations in Taiwan

Abstract: A program of research named Towards an Integrative Biology (TAIB) has recently been promoted by the International Union of Biological Sciences, involving multidisciplinary and interdisciplinary research. Studies of Miscanthus plants which emphasized the TAIB theme were undertaken. Miscanthus species are the most widely distributed and dominant species in Taiwan, growing everywhere from the coastal to mountainous areas, and from agricultural to polluted land. Particularly, the grasses grow well in habitats unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…Although most M. floridulus generally populates coastal regions, it also has been found in high-altitude areas [87]. However, Chou et al [88] found that the M. floridulus that are dominant in Taiwan lowlands could not grow well at 2,600 m.…”
Section: Miscanthus Floridulusmentioning
confidence: 98%
“…Although most M. floridulus generally populates coastal regions, it also has been found in high-altitude areas [87]. However, Chou et al [88] found that the M. floridulus that are dominant in Taiwan lowlands could not grow well at 2,600 m.…”
Section: Miscanthus Floridulusmentioning
confidence: 98%
“…It is also found in the boreal zone (northeastern Siberia 50 N) (Scally et al 2001). These features would have represented important advantages, which might have contributed not only to Miscanthus being trialed through the world, but would have facilitated the understanding of genetic  environmental interactions and allowed empirical breeding (Chou et al 2001). These features would have represented important advantages, which might have contributed not only to Miscanthus being trialed through the world, but would have facilitated the understanding of genetic  environmental interactions and allowed empirical breeding (Chou et al 2001).…”
Section: Origin and Distributionmentioning
confidence: 99%
“…The morphological traits of Miscanthus are sometimes unstable for certain phenotypic traits (Lee 1964a, b, c), allowing the International Plant Name Index (IPNI) and taxonomists to wrongly describe and identify plants. Molecular studies and DNA sequencing may contribute substantially to the clarification of genetic backgrounds (Chou et al 2001;Hodkinson et al 2002a, b, c). To prevent confusion in the literature, Hodkinson and Renvoize (2001) have corrected the "name" as M. Â giganteus "Greef et Deuter."…”
Section: The Morphology Of Miscanthusmentioning
confidence: 99%
“…Incipient species of Miscanthus floridulus and Miscanthus sinensis are ecologically differentiated but connected by gene flow. Miscanthus species (Poaceae), which are C 4 biofuel plants that grow rapidly and are highly resistant to pathogens (Chou et al ., ; Christian et al ., ; Dohleman and Long, ), display high levels of ecological and morphological polymorphisms. The two species are distributed in East Asia, overlapping in southern Japan, Taiwan, and south‐eastern China (Clifton‐Brown et al ., , ).…”
Section: Introductionmentioning
confidence: 98%
“…condensatus in saline habitats along the coastline, and M. sinensis var. glaber in soil containing high copper or sulfur levels (Chou et al ., ), represent local adaptation to an extreme habitat. Patches of these locally adapted variants may expand via their rhizomes, partly explaining the ecological abundance of Miscanthus (Wu et al ., ).…”
Section: Introductionmentioning
confidence: 99%